Description of New Species of Coronostrongylus and Dorcopsistrongylus (Strongylida: Chabertiidae) from Dorcopsis muelleri (Macropodidae) from Kumawa Mountains, West Papua, Indonesia - Purwaningsih, Endang; Dewi, Kartika; Smales, Lesley R. (Zootaxa, 2019)
New species of Coronostrongylus and Dorcopsistrongylus (Strongyloidea: Chabertiidae) are described from Dorcopsis muelleri (Macropodidae) from Kumawa Mountains, West Papua, Indonesia. Coronostrongylus hasegawai n.sp .is most similar to C. spearei, the only other species described from New Guinea, in having 24 longitudinal pleats in the buccal cavity and spicules less than 1,400 long. Coronostrongylus hasegawai differs from C. spearei, in a suite of characters including the shape of the cephalic collar, the proportions of the buccal capsule, the disposition of the bursal rays, the length of the spicules and the proportions of the ovejector. Dorcopsistrongylus supriyatnai n.sp differs from all congeners in lacking large anteriorly directed intestinal diverticula. The genus Coronostrongylus is found in Australia and New Guinea while the genus Dorcopsistrongylus appears to be endemic to New Guinea.